2015
DOI: 10.1007/s11906-015-0559-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium and Cardiovascular Disease

Abstract: Although an essential nutrient, higher sodium intake is associated with increasing blood pressure (BP), forming the basis for current population-wide sodium restriction guidelines. While short-term clinical trials have achieved low intake (<2.0 g/day), this has not been reproduced in long-term trials (>6 months). Guidelines assume that low sodium intake will reduce BP and reduce cardiovascular disease (CVD), compared to moderate intake. However, current observational evidence suggests a J-shaped association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Apart from pharmacological treatment, dietary modification is a fundamental therapy for selfmanagement of diabetes [4]. Previous studies have consistently reported an inverse association between the risk of CVD events and the consumption of individual food items such as fruit [5], vegetables [6], whole grains [7], seafood [8], whereas unprocessed red/processed meat [9] and salt [10] are positively associated. By thinking about the multiple dietary exposures' complexity and interrelations, overall dietary pattern analysis, which involves series methods to assess diets comprehensively, might be more informative about the role of diet for the etiology of diet-related diseases than single food item analysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from pharmacological treatment, dietary modification is a fundamental therapy for selfmanagement of diabetes [4]. Previous studies have consistently reported an inverse association between the risk of CVD events and the consumption of individual food items such as fruit [5], vegetables [6], whole grains [7], seafood [8], whereas unprocessed red/processed meat [9] and salt [10] are positively associated. By thinking about the multiple dietary exposures' complexity and interrelations, overall dietary pattern analysis, which involves series methods to assess diets comprehensively, might be more informative about the role of diet for the etiology of diet-related diseases than single food item analysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tuz tüketimi ile kardiyovasküler hastalık arasındaki ilişkinin değerlendirildiği çalışmalarda, en düşük ve en yüksek risklerin sırasıyla 3-5 g/gün ve <3 g/gün tuz tüketimi ile oluştuğu rapor edilmiştir. 79,80 Kalp hastalarında aşırı tuz kısıtlamasının ölüm riskini artırdığı düşünülmektedir. 81,82 Tuzun sadece sodyumdan ibaret olmadığı, klorun da vücut çalışmasında önemli işlevleri olduğu söylenmektedir.…”
Section: Yetersi̇z Tuz Tüketi̇mi̇unclassified
“…Apart from pharmacological treatment, dietary modi cation is a fundamental therapy for selfmanagement of diabetes [4]. Previous studies have consistently reported an inverse association between the risk of CVD events and the consumption of individual food items such as fruit (Aune et al, 2017), vegetables [6], whole grains [7], seafood [8], whereas unprocessed red/processed meat [9] and salt [10] are positively associated. By thinking about the multiple dietary exposures' complexity and interrelations, overall dietary pattern analysis, which involves series methods to assess diets comprehensively, might be more informative about the role of diet for the etiology of diet-related diseases than single food item analysis [11].…”
Section: Introductionmentioning
confidence: 99%